Photochemical corneal cross-linking: Evaluating the potential of a hand-held biopen - Nadina Usseglio; Julia López de Andrés; Juan Antonio Marchal; Lorenzo Moroni; Daniel Nieto (Materials Today Bio)
The generation of organized 3D tissue constructs that combines cells and photo-crosslinkable biomaterials has been demonstrated using a variety of 3D bioprinting technologies. These technologies have inspired the application for “in situ” bioprinting, resulting on hand-held tools called “Biopens” that can transfer bioprinting capabilities directly into the hands of the surgeons. Here, we have developed and validated a biopen for ophthalmological applications, specifically for corneal stromal regeneration using photochemical corneal crosslinking (CXL), as well as for cell bioprinting and, potentially, for corneal wound healing. We used the biopen to CXL, but also for fast crosslinking processes. Cytotoxicity, cell viability and immunofluorescence experiments were performed with human corneal stroma keratocytes (HCK) loaded inside the proposed bioink compositions. Photochemical cross-linking was performed to evaluate the biopen bioprinting functionality for corneal wound closure in porcine eyes. A full-thickness penetrating incision, 5 mm in length parallel to the limbus and perpendicular to the corneal surface, was made in the enucleated porcine cornea. The mechanical properties of cornea are imitated by tuning the proposed (GelMA/PEGDA/PI) bioink composition and crosslinking parameters, which envisage the potential for being translated to a clinical environment to corneal wound closure.